2020
DOI: 10.3390/w12092586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Loading Rate on Performance and Methanogenic Microbial Communities of a Fixed-Bed Anaerobic Reactor at 4 °C

Abstract: We investigated the feasibility of producing biogas in a fixed-bed anaerobic reactor at 4 °C with a gradual increase in organic loading rate (OLR). Reactor efficiency was highest when OLR was 4.33 kg/m3·d, whereas the reactor acidification occurred when OLR was 4.67 kg/m3·d. The values of methane content, biogas production, chemical oxygen demand (COD) removal rate, biogas production rate, acetic acid content, and propionic acid content were 69.3%, 5.33 L, 59.8%, 1.03 L/OLR, 0.17 g/L, and 1.15 g/L, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Therefore, compared with other wastewaters (e.g., trichloroethylene wastewater and synthetic wastewater), molasses wastewater is more difficult to treat and causes operational issues for reactors performing anaerobic biological treatment. In previous research, we confirmed that fixed-bed anaerobic reactors had impact resistance and high methane content when used to treat molasses wastewater at low temperatures [14,18,22]. However, no study has evaluated fix-bed reactor operation at decreasing temperatures in order to assess the microbial community for molasses wastewater treatment at low temperatures.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Therefore, compared with other wastewaters (e.g., trichloroethylene wastewater and synthetic wastewater), molasses wastewater is more difficult to treat and causes operational issues for reactors performing anaerobic biological treatment. In previous research, we confirmed that fixed-bed anaerobic reactors had impact resistance and high methane content when used to treat molasses wastewater at low temperatures [14,18,22]. However, no study has evaluated fix-bed reactor operation at decreasing temperatures in order to assess the microbial community for molasses wastewater treatment at low temperatures.…”
Section: Introductionsupporting
confidence: 55%
“…The experiments were divided into three operation phases (Table 1), which were characterized by changes in temperature and COD. In order to verify the operating temperature threshold and the methanomicrobiale colonization of the carbon-fiber carrier fixed-bed reactor operating at low temperatures, we confirmed that the fixed-bed reactor could be operated at the low temperatures of 5 • C and 4 • C [14,18], but whether this is the temperature threshold for low-temperature operation has not been confirmed. Therefore, we selected 4 reactors with exactly the same specifications and types for this study.…”
Section: Experimental Protocolmentioning
confidence: 94%
See 2 more Smart Citations
“…This is probably explained by the well-established consortium attained after an extended operation time in industrial operating reactors [147]. Zhao et al [148] studied digestion performance at 4 • C, indicating that the maximum treatment capacity was set at 4.33 g VS/Lr d of OLR. Therefore, low-temperature operating digestion systems may become a low-cost solution for the operation of decentralized reactors with a treatment capacity equivalent to that of more complex mesophilic and thermophilic reactors.…”
Section: Temperature and Digestion Performancementioning
confidence: 99%